1982
DOI: 10.1093/ptj/62.10.1431
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Measuring Trunk Motions in Centimeters

Abstract: A method of measuring trunk motion and two related motions using a tape measure and a stepstool was developed by physical therapists at our hospital. The purpose of this study was to assess the reliability of this method. Three repetitions of six motions performed by 24 subjects were each measured by three physical therapist raters on two separate days. The motions were forward bending, backward bending, right side bending, right rotation, right straight leg raising, and right prone knee bending. Reliability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1
6

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 7 publications
2
68
1
6
Order By: Relevance
“…The ability of one tester to reproduce the recorded values o f another was high for all the situations tested. Indeed i t was higher than that reported in earlier studies (2,3,6,9,11 The reproducibility of the measurements was higher in all 5ituations when the subject stood in the test apparatus than i t was when he/she stood freely on the floor. This is, however, not supported by the way they reacted during the tests.…”
Section: Discussioncontrasting
confidence: 53%
“…The ability of one tester to reproduce the recorded values o f another was high for all the situations tested. Indeed i t was higher than that reported in earlier studies (2,3,6,9,11 The reproducibility of the measurements was higher in all 5ituations when the subject stood in the test apparatus than i t was when he/she stood freely on the floor. This is, however, not supported by the way they reacted during the tests.…”
Section: Discussioncontrasting
confidence: 53%
“…Within our study, we did not find any statistically significant correlation between the modified Schober test and MRI findings. Clinical studies have found the reliability of the FTFD ranging from low [31] to high [4,15,19,39]. In our study, the relationship between structural changes of the lumbar spine and the FTFD was only weakly correlated to endplate changes on level L4-5.…”
Section: Mobility Testsmentioning
confidence: 49%
“…The modified Schober and the FTFD were described previously [4,15,19,27,31,39]. For the LB, the participants were told to slowly bend from the upright position to the side with their hand running down a vertical ruler.…”
Section: Testing Proceduresmentioning
confidence: 99%
“…The above-mentioned results of the t test and nonparametric analysis were confirmed by correlation analysis ( Measurements of forward bending demonstrated good reliability and validity to asses trunk mobility in the past [25][26][27][28][29].…”
Section: Correlation Analysismentioning
confidence: 89%